Postmortem Analysis of Ethyl Alcohol Concentration in Blood, Urine, Muscle and Bile - Okulevičiūtė, Agnė; Chmieliauskas, Sigitas; Laubner-Sakalauskienė, Gabija; Badaras, Robertas; Laima, Sigitas; Vasiljevaitė, Diana; Stasiūnienė, Jurgita (Acta medica Lituanica, 2024)
Introduction: The determination of ethyl alcohol concentration in body fluids is an important investigation in forensic practice. To avoid postmortem changes in blood alcohol concentration, the test substance must be transported in special media enriched with sodium fluoride or potassium oxalate. When interpreting changes in concentrations in the body, it is important to assess not only the blood but also other body fluids or tissues. Materials and methods: A retrospective study was conducted from 2016 to 2023, evaluating data from nonconsecutive 378 autopsies from the State Forensic Medical Service of Lithuania. The study analyzed ethyl alcohol concentrations in blood, urine, muscle and bile. Toxicological data were processed using R commander statistical software. The study aimed to assess the changes, patterns, and correlations of ethyl alcohol concentrations in different body fluids after death. Results: When the ethyl alcohol concentrations of the different body fluids from the autopsies were evaluated, the urine ethyl alcohol concentration was in 86% cases higher than the blood ethyl alcohol concentration, with a mean difference of 0.51‰. There is a strong correlation between blood and urine ethyl alcohol concentrations, r = 0.93, p < 0.05. The ethyl alcohol concentration in muscle was 75% higher than in blood with a mean difference of 0.06‰. Ethyl alcohol concentration in bile was 90% higher than in blood with a mean difference of 0.14‰. The difference between ethyl alcohol concentrations in bile and muscle was not significant, with a mean difference of 0.07‰. Conclusions: In addition to blood and urine, muscle and bile samples may be taken at autopsy to detect ethyl alcohol. The results of the study show that there may be differences in the levels of ethyl alcohol in different body fluids after death. These data are therefore important for the assessment of ethyl alcohol concentrations in both clinical and forensic practice.